2005
DOI: 10.1016/j.cardiores.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone increases T-type calcium channel expression and in vitro beating frequency in neonatal rat cardiomyocytes

Abstract: Aldosterone modulates the expression of cardiac voltage-operated Ca2+ channels and accelerates beating in cultured neonatal rat ventricular myocytes. This chronotropic action of aldosterone appears to be linked to increased T channel activity and could contribute to the deleterious effect of an excess of this steroid in vivo on cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 49 publications
10
75
1
4
Order By: Relevance
“…Furthermore, non-genomic effects of aldosterone on I Ca,L were excluded and co-incubation with spironolactone blunted upregulation of I Ca,L , possible effects of spironolactone on the channel´s biophysical properties were not described. Similar effects of aldosterone on current density and, respectively, the missing effect on biophysical properties of I Ca,L were obtained in ventricular neonatal rat cardiomyocytes (Lalevee et al 2005). Correlation of I Ca,L current density and plasma level of aldosterone was demonstrated Briggs et al 1959 Spironolactone prolongs action potential duration in isolated rabbit atrium.…”
Section: Genomic Effects On the Ventricular Levelsupporting
confidence: 54%
“…Furthermore, non-genomic effects of aldosterone on I Ca,L were excluded and co-incubation with spironolactone blunted upregulation of I Ca,L , possible effects of spironolactone on the channel´s biophysical properties were not described. Similar effects of aldosterone on current density and, respectively, the missing effect on biophysical properties of I Ca,L were obtained in ventricular neonatal rat cardiomyocytes (Lalevee et al 2005). Correlation of I Ca,L current density and plasma level of aldosterone was demonstrated Briggs et al 1959 Spironolactone prolongs action potential duration in isolated rabbit atrium.…”
Section: Genomic Effects On the Ventricular Levelsupporting
confidence: 54%
“…24,[27][28][29] Therefore, targeting aldosterone synthesis and release may be clinically important in preventing cardiovascular disease. Ca 2+ ions are conveyed through the T-type Ca channel to the mitochondria, where they activate aldosterone synthesis, which in turn stimulates T-type Ca channel expression, 30,31 creating a positive feedback loop of aldosterone biosynthesis in adrenal cells. Efonidipine, another T-type CCB, has been shown to inhibit aldosterone synthesis and secretion in vitro, 9 as well as in both healthy subjects and patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…73 The mechanisms underlying the generation of arrhythmias remain unclear, although it has been shown that in normal rat neonatal cardiomyocytes, aldosterone increases L-type calcium current amplitude in ventricular myocytes. 74 Aldosterone exerts opposing effects on T channel…”
Section: Aldosterone Actions In the Heartmentioning
confidence: 99%